Propuesta de mejora al modelo de gestión de PETROAMAMZONAS EP para reducir la producción diferida en el bloque 15 - Carvajal Camacho, Mario Fernando (2014)
In this research, we propose administrative solutions which will contribute to the reduction of deferred production, caused by the unscheduled interruptions of crude oil wells in Bloque 15 of Petroamazonas EP. The methodology used to evaluate the Model Management of PAM EP was based on the Model of Excellence in the Malcolm Baldrige Management where PAM EP obtained 486,19 points. Out of the 6 criterias of process, including: Measurement, Analysis and Knowledge Management, PAM EP reached the highest value of 65,62%. Based on the two other criterias which PAM EP obtained the lowest score, Orientation towards the Customer and Market, 21,28 points and Process Management: 7,44 points, we must establish specific strategies to overcome this deficit.